Phenotypic tumour cell plasticity as a resistance mechanism and therapeutic target in melanoma. (May 2016) - Roesch, Alexander; Paschen, Annette; Landsberg, Jenny; Helfrich, Iris; Becker, Jürgen C.; Schadendorf, Dirk
Abstract: Despite the recent success of MAPK and immune checkpoint inhibitors in advanced melanoma, intrinsic and acquired resistance mechanisms determine the efficacy of these therapeutic approaches. Therapy resistance in melanoma is not solely driven by genetic evolution, but also by epigenetically driven adaptive plasticity. Melanoma cells are shifting between different transcriptional programs, cell cycle states and differentiation phenotypes reflecting a highly dynamic potential to adapt to various exogenous stressors including immune attack or cancer therapies. This review will focus on the dynamic interconversion and overlap between different melanoma cell phenotypes in the context of therapy resistance and a dynamically changing multicellular microenvironment. Highlights: Melanoma is a highly heterogeneous tumor with a functionally diverse spectrum of cell subpopulations and phenotypes. Therapy resistance in melanoma is not only driven by genetic evolution, but also by adaptive, phenotypic cell plasticity. Reciprocal interactions between melanoma and immune cells promote melanoma cell plasticity and drive therapy resistance. Melanoma cells dynamically shift between different transcriptional programs, cell cycle states and differentiation phenotypes.